Characterization and toxicity of zinc aluminium layered double hydroxide-levodopa nanocomposite - Kura, Aminu Umar (2014)
Levodopa is the drug of choice in the treatment of Parkinson's disease (PD), a neurodegenerative disorder with no direct fatal outcome. However, peripheral metabolism and poor brain delivery when given alone is a setback of levodopa in PD management. Layered double hydroxide (LDH) is an inorganic nanocomposite that harbors drug between its two layered sheets. It has sustained, continuous and slow release ability, proven to be biocompatible and less toxic in most cases than conventional drug systems. Here, an organic–inorganic nanocomposite material containing levodopa was synthesized to evaluate for a sustain release and decrease toxicity potential. The resulting nanocomposite was composed of the organic moiety, levodopa, sandwiched between Zn/Al-LDH inorganic interlayers. The basal spacing of resulting nanocomposite was 10.9 Å. Estimated loading of levodopa in the nanocomposite was approximately 16% (w/w). A Fourier transform infrared study showed that the absorption bands of the nanocomposite were characteristic of both levodopa and Zn/Al-LDH, and that the intercalated organic moiety in the nanocomposite was more thermally stable than free levodopa. The resulting nanocomposite showed sustained-release properties, caused better viability of fibroblast (3T3) cells than pure levodopa after 72h of exposure. Further coating of Tween-80 of the levodopa-LDH nanocomposite was achieved through the oxygen of C=O group of Tween-80 with the layered of levodopa-LDH nanocomposite. The X-ray diffraction technique indicates that the Tween-levodopa-LDH nanocomposite was an aggregated structure. From the thermogravimetric analysis data, the loading of Tween-80 coating on the surface of levodopa-LDH nanocomposite was 5.4%. The release of levodopa from Tween-levodopa-LDH nanocomposite was slower compared to that from levodopa-LDH nanocomposite,presumably due to the retarding and shielding effect. A dopaminergic cell line (PC12) showed improved viability with Tween-80 coated levodopa-LDH nanocomposite treatment by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Levodopa-LDH nanocomposite demonstrated lesser dose and time-dependent toxicity on a dopaminergic cell (PC12) compared to pristine levodopa. The cytoskeletal structure of PC 12 was preserved at the IC50 concentration of the nanocomposite 178.67±2.6 μg/mL and pure levodopa 49.37±1.2 μg/mL. Metabolism of the nanocomposite was shown via levodopa metabolite (HVA) release from the treated neuronal cell (PC12). Acute oral toxicity study of nanocomposite on Sprague Dawley rats at a dose of 2000 mg/kg produced neither mortality nor toxicity after 14 days of treatment. Animal treated with nanocomposite gained weight (p<0.05). Biochemical analysis of renal and liver functions showed no significant difference between rats treated with nanocomposite and the controls. There was neither any gross lesion nor histopathological change observed in various organs. Repeated dose study with nanocomposite at 5 mg/kg and 500 mg/kg for 28 days showed no sign or symptom of toxicity. Body weight gain, feeding, water intake,general survival, and organosomatic index were not significantly different between control and treatment groups. The differences in AST/ALT of 500 mg/kg levodopananocomposite (0.32±0.12) and 500 mg/kg LDH-nanocomposite treated rats (0.34±0.12) were statistically significant (p<0.05) compared to the control (0.51±0.07). The histology of liver, spleen and brain were found to be of similar in morphology in both control and experimental groups. The kidneys of 500 mg/kg treated rats treated with 500 mg/kg body weight of levodopa-nanocomposite or LDH- nanocomposite were found to have slight inflammatory changes, notably leukocyte infiltration around the glomeruli. The ultra-structure of the neurons from the substantia nigra of nanocomposite-treated rats was similar to those receiving only normal saline. An anti-Parkinsonian drug (levodopa) was successfully intercalated into the interlayers of zinc aluminium nanodelivery system via co-precipitation method. The nanocomposite was shown to be safe in animal at single 2000 mg/kg dose taken orally, but some changes were noted in the kidney and liver after repeated dose treatment with 500 mg/kg body weight of the nanocomposites. Further assessment through chronic toxicity study is needed to determine the safety profile of long term treatment with the nanocomposite.